Effects of Myofascial Release in chronic low back pain - review papers - Piotr Ożog; Dawid Natański; Aleksander Goch; Magdalena Weber-Rajek; Walery Zukow; Agnieszka Radzimińska (Kazimierz Wielki University, 2018)
Admission Dysfunctions of the lumbosacral spine are among the most common problems related to the movement of contemporary society throughout the world, and its incidence increases with age. In recent years, increased interest in the issues fascia, which until recently was neglected in the etiology of low back pain. One of the therapeutic options that can be applied in the case of chronic pain syndrome lumbar-sacral spine techniques are easing myofascial (ang. Myofascial release, MFR), which is one of the latest methods in the field of manual medicine. Objective of the work The aim of the work was overview AD recently published study on the effectiveness of techniques easing myofascial pain in chronic lumbar-sacral spine. Material and methods To find the current investigate research (publications of the last 5 years) dedicated to MFR in the treatment of chronic pain, lumbar-sacral spine searched the following databases: PubMed, PEDro (Physiotherapy Evidence Database), ScienceDirect and Academic Search Premier. The following keywords: myofascial release, myofascial release therapy, myofascial pain, chronic low back pain. Results 9 qualified to review the studies investigating the effect of loosening myofascial pain and range of motion, functional limitations, muscles, as well as the quality of life in people with chronic pain lumbosacral spine. Conclusions The results of this review show that there is little research on the MFR employs treat ailments low back pain lumbar - sacral. Based on the studies included in this review can be concluded that the MFR can be an effective treatment for back pain lumbar - sacral, but there is a need for further research with a well-developed research procedure that will allow the standardization of this therapeutic method.